A Survey on Scope of Poultry Farming as Livelihood in Attappadi Tribal Settlements with Special Reference to Agali Panchayat-Kerala - P.G.Vineetha; M.Sarath; B.Ajith Babu; Stella Cyriac and M.A.Nisamol
A study of the existing traditional poultry production system, its benets and drawbacks in the Attappadi tribal area was conducted using a baseline survey in November 2016. This survey focused mainly on existing housing systems, feeding, health, marketing of chickens and availability of poultry products. The major constraints reported were lack of good shelter, quality feed, predator attack, diseases and lack of continuous monitoring from the government authorities on the implemented projects. In nutshell, need based projects with continuous monitoring will improve the socio-economic status of the tribal people by meeting high nutritional demand of the area and women empowerment through financial security.